2016
DOI: 10.18388/abp.2016_1296
|View full text |Cite
|
Sign up to set email alerts
|

Amentoflavone prevents sepsis-associated acute lung injury through Nrf2-GCLc-mediated upregulation of glutathione

Abstract: Sepsis is a serious medical problem and is one of the main causes of high mortality in intensive care units. Fifty percent of patients with severe sepsis will develop acute lung injury (ALI). Amentoflavone (AMF) is a polyphenolic compound possessing potent anti-inflammatory activities. The study aimed to explore the protective effects of AMF against ALI in cecal ligation and puncture (CLP)-induced septic rats. The results showed that AMF administration protected against septic ALI, as reflected by marked ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…Mervyn et al and Novelli et al [ 26 28 ] demonstrated that antioxidant depletion such as glutathione (GSH) was one of the most important characteristics in septic patients, which may ultimately lead to severe oxidative stress. Upregulation and activation of GSH could final ameliorate inflammation and histological injury of lung tissues [ 29 ]. In our study, we also observed the same phenomenon that the quantity of GSH was declined significantly, but the quantity of GSH was enhanced after XBJ treatment, indicating that XBJ may be a therapeutic option for sepsis-induced ALI through alleviating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mervyn et al and Novelli et al [ 26 28 ] demonstrated that antioxidant depletion such as glutathione (GSH) was one of the most important characteristics in septic patients, which may ultimately lead to severe oxidative stress. Upregulation and activation of GSH could final ameliorate inflammation and histological injury of lung tissues [ 29 ]. In our study, we also observed the same phenomenon that the quantity of GSH was declined significantly, but the quantity of GSH was enhanced after XBJ treatment, indicating that XBJ may be a therapeutic option for sepsis-induced ALI through alleviating oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [ 30 ] found that sphingosine exerted a critical role in signal transduction and participated in the process of growth, senescence, differentiation, and apoptosis. Published articles [ 26 , 27 , 29 ] showed that sphingolipid metabolism also played a critical role in oxidative stress. When sepsis occurs, it is in oxidative status, which causes severe cell membrane damage and sphingolipid loss.…”
Section: Discussionmentioning
confidence: 99%
“…Existed research has indicated that induced NQO1 and HO1 levels were accompanied with the accumulation NRF2 in nucleus, thus protecting cells against oxidative damage ( Zhang et al, 2008 ). In sepsis-induced acute lung injury, up-regulation of the NRF2-GCLC signaling pathway was associated with enhancement of GSH and reduction of oxidative damage ( Zong & Zhang, 2017 ). Consistent with former research, this study found the elevated mRNA and protein levels of NQO1, GCLC and HO1 by NRF2 overexpression, suggesting that NRF2 could promote the expression of NRF2 when it stimulated the cell.…”
Section: Discussionmentioning
confidence: 99%
“…[28,[36][37][38][39][40] In the histopathological evaluation, severe tissue damage was reported. [38] These results are also consistent with the findings we obtained in our sepsis model. It has also been reported that there were increases in the levels of caspase 3 and Bax/BcL 2 in the lungs.…”
Section: Discussionmentioning
confidence: 99%